2008
DOI: 10.1038/oby.2008.421
|View full text |Cite
|
Sign up to set email alerts
|

The FTO Gene and Obesity in a Large Eastern European Population Sample: The HAPIEE Study

Abstract: Variants in the FTO (oxoglutarate‐dependent nucleic acid demethylase) gene have been associated with the BMI determination in Western European and North American populations. To widen the geographical coverage of the FTO studies, we have analyzed the association between the FTO gene variant rs17817449 (G>C) and obesity in a Slavic Eastern European population. A total of 3,079 males and 3,602 females 45–69 years old were randomly selected from population registers of seven Czech cities. We examined three indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 14 publications
3
37
4
1
Order By: Relevance
“…Associations of the FTO gene polymorphism with obesity have been examined in several studies with conflicting results [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The finding in which the association of the FTO gene polymorphism with obesity seems to depend on moderate to high-intensity PA might explain the inconsistencies in previous studies.…”
Section: Lifestyle-dependent Association Of the Common Fto Gene Polymcontrasting
confidence: 45%
See 2 more Smart Citations
“…Associations of the FTO gene polymorphism with obesity have been examined in several studies with conflicting results [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The finding in which the association of the FTO gene polymorphism with obesity seems to depend on moderate to high-intensity PA might explain the inconsistencies in previous studies.…”
Section: Lifestyle-dependent Association Of the Common Fto Gene Polymcontrasting
confidence: 45%
“…Among such polymorphisms, the polymorphism rs9939609 has been the most studied and wellannotated polymorphism with the allele A to be associated with obesity phenotype [9][10][11][12][13][14][15][16][17][18]. Although the association of the FTO gene with obesity is observed across many different ethnic populations [5][6][7][8][9][10][11][12][13][14][15][16][17][18], there study population are shown in Table 1. Individuals who had a BMI of more than 25 kg/m 2 were considered obese (n=794).…”
Section: Association Of the Commonmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past year exciting new evidence from genome-wide association studies reproducibly highlighted the FTO SNP allelic distribution as a predictive factor for obesity in various human populations (Dina et al 2007, Al-Attar et al 2008, Freathy et al 2008, Hotta et al 2008, Hubacek et al 2008, Willers et al 2008). The mechanisms underlying the physiological relationship between FTO allelic variations and alterations of body weight homeostasis are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A set of single-nucleotide polymorphisms (SNPs) in the first intron of FTO are strongly associated with adiposity/obesity and related phenotypes. [7][8][9][10][11][12][13][14][15][16][17] It has been shown that adults homozygous for the risk allele at rs9939609 weigh on average B3 kg more than those homozygous for the other allele. 7 FTO genotype has also been reported to be associated with adiposity in children [7][8][9] and the strength of its influence to increase during childhood.…”
Section: Introductionmentioning
confidence: 99%